Accounting for Environmental Performance in Achieving the Social Responsibility of Economic Units in the Light of Contemporary Accounting Problems - Baychan, Rajaa Sadiq (Journal of University of Human Development, 2018)
<span data-sheets-value=""1":2,"2":"The objective of the research is to strive to highlight the role of economic units in contributing to the welfare of society by improving the environmental conditions and reducing the negative effects caused by its activity to the surrounding environment by reducing pollution and achieving economic development. More productive by developing their technical and productive capacities and providing industrial security for them. It is important to note that the provision of health, social and cultural care to them and to their families creates confidence, belonging and self-denial towards economic unity. The problem of research has been shaped by questions about the general criteria that can be adopted by the economic units and the appropriate data and statistics in the light of contemporary accounting problems. The development of specific questions to measure the role of environmental performance may complicate the possibility of applying CSR and delay their use for CSR applications in the absence of clear, quantifiable indicators. The research has reached a number of results, the most important of which is that the laws of many countries hold individuals accountable for the pollution and noise they cause to society and the damage they cause to public facilities and properties. This concept should apply to companies whose activities directly or indirectly harm the lives of citizens, Such as water, air and public health. Therefore, an important measure of efficiency of the company and the priority that can be enjoyed by its products in society is to reduce the damage to this community in any way. Accountability of social responsibility, the current research being a simple addition within the scope of Iraqi companies, is a tool for monitoring this aspect."" data-sheets-userformat=""2":8403839,"3":[null,0],"4":[null,2,16777215],"5":"1":["1":2,"2":0,"5":[null,2,11184810],"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"6":"1":["1":2,"2":0,"5":[null,2,11184810],"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"7":"1":["1":2,"2":0,"5":[null,2,11184810],"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"8":"1":["1":2,"2":0,"5":[null,2,11184810],"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"9":1,"11":0,"12":0,"14":[null,2,0],"15":"Arial, sans-serif","16":10,"26":400">The objective of the research is to strive to highlight the role of economic units in contributing to the welfare of society by improving the environmental conditions and reducing the negative effects caused by its activity to the surrounding environment by reducing pollution and achieving economic development. More productive by developing their technical and productive capacities and providing industrial security for them. It is important to note that the provision of health, social and cultural care to them and to their families creates confidence, belonging and self-denial towards economic unity. The problem of research has been shaped by questions about the general criteria that can be adopted by the economic units and the appropriate data and statistics in the light of contemporary accounting problems. The development of specific questions to measure the role of environmental performance may complicate the possibility of applying CSR and delay their use for CSR applications in the absence of clear, quantifiable indicators. The research has reached a number of results, the most important of which is that the laws of many countries hold individuals accountable for the pollution and noise they cause to society and the damage they cause to public facilities and properties. This concept should apply to companies whose activities directly or indirectly harm the lives of citizens, Such as water, air and public health. Therefore, an important measure of efficiency of the company and the priority that can be enjoyed by its products in society is to reduce the damage to this community in any way. Accountability of social responsibility, the current research being a simple addition within the scope of Iraqi companies, is a tool for monitoring this aspect.